Junior high school students’ mathematical reasoning skills on integer using PMRI and collaborative learning - Mutia Khoirunnisa; Ratu Ilma Indra Putri (Universitas Hamzanwadi, 2022)
Students need to have good mathematical reasoning skills when learning integer material. The utilization of video media and collaborative learning through the PMRI technique can be used in learning activities to improve mathematical reasoning skills. This study aims to determine mathematical reasoning skills after implementing the learning process using video media with the PMRI approach and collaborative learning integer material for class VII students. This study is descriptive research in which participants are pupils in class VII SMP Srijaya Negara Palembang has 23 students (10 females and 13 males). This study consisted of two meetings. The first meeting focused on the learning process using video material with PMRI and collaborative learning. The second meeting was used to test the results. This study employs observational data gathering techniques, written tests, interviews, and descriptive data analysis approaches. The findings of a study are combining video media and the PMRI technique and collaborative learning on integer subjects in class VII. The skills of students in class VII to reason mathematically was discovered. On the subject of excellent integers, SMP Srijaya Negara Palembang students scored an average of 69.61. The sign of creating assumptions appears to be the most frequent in this study, while the indicator of concluding appears to be the least frequent. Students' mathematical thinking skills can be improved by using video media in conjunction with PMRI and Collaborative Learning during the learning process.